El autobus escolar - Crews, Donald (New York, NY : Scholastic, Inc., 1991)
Follow the progress of school buses as they take children to school and bring them home again.
Translation of: School bus.
Keywords: School buses -- Juvenile fiction; Children's stories, American; Spanish language materials; Fiction